Dose health education on dementia prevention have more effects on community residents when a community physician/nurse leads it? A cross-sectional study - Gong, De; Peng, Yan; Liu, Xiao; Zhang, Jinying; Deng, Menghui; Yang, Tiantian; Yang, Yanni (Frontiers in Public Health, 2023)
Background: Dementia is a growing public health concern worldwide. Community residents still have limited knowledge about dementia prevention, although many sources are accessible for individuals to acquire knowledge. Methods: A questionnaire-based survey was conducted in five communities in Chongqing, China, between April and September 2020. Participants were divided into three groups according to the dementia-related education they received: physician/nurse-led, mass media, and no relevant education. Covariance analysis was performed to determine the differences among the three groups in knowledge, motivation, and lifestyle, with the covariate of MoCA scores (education-adjusted). Results: Of the 221 participants, 18 (8.1%) received physician/nurse-led education, 101 (45.7%) received only mass media education, and 102 (46.2%) did not receive any relevant education regarding dementia prevention. Participants who only received mass media education had a higher level of education (t=5.567, p=0.004) and cognitive function (t=13.978, p<0.001). The analysis of covariance showed that compared with participants who received no relevant education, those who received physician/nurse-led education had higher levels of knowledge, perceived benefits, and better lifestyle, and those who received mass media education had lower perceived barriers; however, higher levels of cues to action, general health motivation, self-efficacy, and lifestyle (all p <0.05). Conclusions： The popularization of dementia-related education was not ideal for communities. Physician/nurse-led education plays a vital role in providing knowledge and promoting lifestyles for dementia prevention, but may not motivate community residents. Mass media education may help encourage residents and promote their lifestyles.